Modafinil for the Treatment of Methamphetamine Dependence - Anderson, Ann L. (2011)
AIM: Modafinil was tested for efficacy in decreasing use in methamphetamine-dependent participants, compared to placebo. METHODS: This was a randomized, double-blind, placebo-controlled study, with 12 weeks of treatment and a 4-week follow-up. Eight outpatient substance abuse treatment clinics participated in the study. There were 210 treatment-seekers randomized, who all had a DSM-IV diagnosis of methamphetamine dependence; 68 participants to placebo, 72 to modafinil 200mg, and 70 to modafinil 400mg, taken once daily on awakening. Participants came to the clinic three times per week for assessments, urine drug screens, and group psychotherapy. The primary outcome measure was a methamphetamine non-use week, which required all the week's qualitative urine drug screens to be negative for methamphetamine. RESULTS: Regression analysis showed no significant difference between either modafinil group (200 or 400mg) and placebo in change in weekly percentage having a methamphetamine non-use week over the 12-week treatment period (p=0.53). Similarly, a number of secondary outcomes did not show significant effects of modafinil. However, an ad-hoc analysis of medication compliance, by urinalysis for modafinil and its metabolite, did find a significant difference in maximum duration of abstinence (23 days vs. 10 days, p=0.003), between those having the top quartile of compliance (>85% urines modafinil +, N=36), and the lower three quartiles of modafinil 200 and 400mg groups (N=106). CONCLUSIONS: Although these data suggest that modafinil, plus group behavioral therapy, was not effective for decreasing methamphetamine use, the study is probably inconclusive because of inadequate compliance with taking medication.